Application of Three-Dimensional Models on Spherical-Radial Filtration the Skin Zone - Dadash-zada, X.I.; Gadashova, E.V. (Herald of Azerbaijan Engineering Academy, 2023)
Various models are used to determine the main filtering parameters. With the help of these models, the flow rate, pressure distributions, reservoir and well permeability are determined. Note that the complexity of the considered oil production processes makes it possible to mathematically describe the filtration process. However, when predicting technological indicators for designing the development of oil fields, rather simple models built on a single basis turn out to be the most acceptable. These models make it possible to carry out the most correct comparative analysis of various methods for increasing gas recovery, to implement multivariate systems to select the optimal development option, and to systematize the initial information.